The Impact of Group Identity on Coalition Formation - Laroze-Prehn, D (SAGE Publications Ltd, 2020)
Bargaining and coalition building are a central part of modern politics. We argue that majoritarian bargaining is important for the formation of coalitions and that group-identity preferences have an impact on partner selection. We tested the effect of gender, race, and ideological distance in a majority-rule bargaining experiment and found that ideological distance significantly affected the likelihood and amount offered to potential partners. We concluded that formateurs are not necessarily purely rational actors pursuing policy goals and/or the benefits of office. Rather, they also care about the identity of their partners, preferring others who are like themselves. © The Author(s) 2020.
Keywords: Coalition formation; laboratory experiments; Baron and Ferejohn model; legislative bargaining; social identity